Diagnostic accuracy of random massively parallel sequencing for non‐invasive prenatal detection of common autosomal aneuploidies: a collaborative study in Europe. (12th December 2013) - Stumm, Markus; Entezami, Michael; Haug, Karsten; Blank, Cornelia; Wüstemann, Max; Schulze, Bernt; Raabe‐Meyer, Gisela; Hempel, Maja; Schelling, Markus; Ostermayer, Eva; Langer‐Freitag, Sabine; Burkhardt, Tilo; et al.
ABSTRACT Objective The objective of this study is to validate the diagnostic accuracy of a non‐invasive prenatal test for detecting trisomies 13, 18, and 21 for a population in Germany and Switzerland. Methods Random massively parallel sequencing was applied using Illumina sequencing platform HiSeq2000. Fetal aneuploidies were identified using a median absolute deviation based z‐score equation. A bioinformatics algorithm based on guanine‐cytosine normalization was applied after the data were unblinded. Results of massively parallel sequencing and invasive procedures were compared. Results Overall, 40/42 samples were correctly classified as trisomy 21‐positive, including a translocation trisomy 21 [46, XY, der(13;21), +21] and a structural aberration of chromosome 21 [46, XX, rec(21)dup(21q)inv(21)(p12q21.1)] but not including a low percentage mosaic trisomy 21 [47, XY, +21/46, XY], [sensitivity: 95.2%; one‐sided lower confidence limit: 85.8%]; 430/430 samples were correctly classified as trisomy 21‐negative (specificity: 100%; one‐sided lower CL: 99.3%). Using a new bioinformatics algorithm with guanine‐cytosine normalization, detection of trisomy 21 was facilitated, and five of five trisomy 13 cases and eight of eight trisomy 18 cases were correctly identified. Conclusion Our newly established non‐invasive prenatal test allows detection of fetal trisomies 13, 18, and 21 with high accuracy in a population in Germany and Switzerland. © 2013 John Wiley & Sons, Ltd.